Riverine flood modeling analysis of Cabanatuan City area using a 1D-2D hydraulic model - Hokson, Jose Angelo A.
This study aims to assess the behavior of riverine flooding in Cabanatuan City through riverine flood flow hydraulic analysis for a selected extreme rainfall event (Typhoon Pedring). This was accomplished through secondary data analysis - topographic data (digital elevation models), river discharge data, etc. (from concerned agencies and online repositories) - and through numerical modeling analysis using the 1D-2D HEC-RAS unsteady flood model. The hydraulic model, which covers the political area of Cabanatuan City and portions of the Municipalities of General Natividad and Santa Rosa within its computational domain, was calibrated and validated using various values of Manning's n representing overland flow resistance during Typhoon Pedring. Flood maps of flood depth, flood extent, flood arrival time, and flood duration were generated accordingly from the results of the numerical simulation. Results demonstrated the following hydraulic properties of flood flow over Cabanatuan area: (1) the generated flood model for the study area are within acceptable accuracy; (2) peak discharge is reduced downstream, with approximately 3600 cms difference, as a consequence of flood inundation over the study area; (3) a ten year return period storm already causes riverine flood depths as high as 10.39 m along the main channel and 8.36 m at the flow area; (4) a ten-year return period storm already causes riverine flooding to 48 barangays of Cabanatuan City; (5) a ten-year return period storm causes riverine flooding that reaches its full extent within 65 hours from the start of rainfall; (6) the duration of flooding over the study area is highly variable, reaching 76 hour-duration at some non-river areas; and (7) overland features of the study area, like road embankments, are shown to affect flood flow movement. With the use of hydraulic modeling analysis, a hydraulic representation of the study area was created for assessing the hydraulics of riverine flood flow over Cabanatuan City in aid of possible flood management decision-making.